THE RELATIONSHIP BETWEEN READING COMPREHENSION ABILITY AND READING HABITS TOWARDS STORY WRITING SKILLS - Roihatul Parida Maulidi; Tatu Hilaliyah; Ujang Jamaludin (Jurnal Cakrawala Pendas, 2025)
This research is motivated to find out the relationship between reading ability and writing skills. The objectives of this study are (1) to explain the relationship between students' reading comprehension ability and the skills of writing short stories of elementary school students (2) to explain the relationship between students' reading habits and the skills of writing short stories of elementary school students (3) to explain the relationship between reading comprehension ability and students' reading habits with the skills of writing stories based on pictures of grade IV elementary school students. Learners can write stories must have insight and abundant vocabulary. In realizing the activity of writing stories, it is related to reading comprehension skills and reading habits every day. Because when students have good reading comprehension, it will produce a story where each paragraph connects to one. In addition, the habit of reading will also generate vocabulary and sentences that can be a reference for writing stories. The method used in this research is correlation research. The types and sources of data used are quantitative data, this research was conducted on grade IV students of SDIT IQRA Serang City. Data collection techniques are using tests and questionnaires. The significant value (0.035) is smaller than α 0.05. Because the value of r count> the value of r table, namely 0.408> 0.312, H0 is accepted, meaning that there is a positive and significant relationship between Reading Comprehension Ability and Reading Habits on Story Writing Skills.